Dlk1 is a negative regulator of emerging hematopoietic stem and progenitor cells - Bahar Mirshekar-Syahkal; Esther Haak; Gillian M. Kimber; Kevin van Leusden; Kirsty Harvey; John O'Rourke; Jorge Laborda; Steven R. Bauer; Marella F. T. R. de Bruijn; Anne C. Ferguson-Smith; Elaine Dzierzak; Katrin Ottersbach (Haematologica, 2013)
The first mouse adult-repopulating hematopoietic stem cells emerge in the aorta-gonad-mesonephros region at embryonic day (E) 10.5. Their numbers in this region increase thereafter and begin to decline at E12.5, thus pointing to the possible existence of both positive and negative regulators of emerging hematopoietic stem cells. Our recent expression analysis of the aorta-gonad-mesonephros region showed that the Delta-like homologue 1 (Dlk1) gene is up-regulated in the region of the aorta-gonad-mesonephros where hematopoietic stem cells are preferentially located. To analyze its function, we studied Dlk1 expression in wild-type and hematopoietic stem cell-deficient embryos and determined hematopoietic stem and progenitor cell activity in Dlk1 knockout and overexpressing mice. Its role in hematopoietic support was studied in co-culture experiments using stromal cell lines that express varying levels of Dlk1. We show here that Dlk1 is expressed in the smooth muscle layer of the dorsal aorta and the ventral sub-aortic mesenchyme, where its expression is dependent on the hematopoietic transcription factor Runx1. We further demonstrate that Dlk1 has a negative impact on hematopoietic stem and progenitor cell activity in the aorta-gonad-mesonephros region in vivo, which is recapitulated in co-cultures of hematopoietic stem cells on stromal cells that express varying levels of Dlk1. This negative effect of Dlk1 on hematopoietic stem and progenitor cell activity requires the membrane-bound form of the protein and cannot be recapitulated by soluble Dlk1. Together, these data suggest that Dlk1 expression by cells of the aorta-gonad-mesonephros hematopoietic microenvironment limits hematopoietic stem cell expansion and is, to our knowledge, the first description of such a negative regulator in this tissue.